The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3748/wjg.v19.i27.4344
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of adherence for tumor necrosis factor-α inhibitors in Crohn’s disease and rheumatoid arthritis: Results of a systematic review

Abstract: One-third of both CD and RA patients treated with TNF-α inhibitors are non-adherent. Female gender was consistently identified as a negative determinant of adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 29 publications
2
62
1
2
Order By: Relevance
“…Three studies showed that in CD the adherence rate for infliximab (72%) was higher compared to that of adalimumab (55%), with a relative risk of 1.61 (95% CI: 1.27–2.03), whereas in RA adherence to adalimumab (67%) was higher compared to that of infliximab (48%) and etanercept (59%), with a relative risk of 1.41 (95% CI, 1.3–1.52) and 1.13 (95% CI, 1.10–1.18), respectively. In another comparative study, the RA adherence to infliximab was higher than with etanercept and adalimumab 33. In contrast, in a Swiss observational cohort of patients with RA (N=2,364) treated with at least one course of anti-TNF therapy from 1997 to 2006, the discontinuation rate was significantly higher among patients treated with infliximab compared with those treated with etanercept or adalimumab 34…”
Section: Discussionmentioning
confidence: 92%
“…Three studies showed that in CD the adherence rate for infliximab (72%) was higher compared to that of adalimumab (55%), with a relative risk of 1.61 (95% CI: 1.27–2.03), whereas in RA adherence to adalimumab (67%) was higher compared to that of infliximab (48%) and etanercept (59%), with a relative risk of 1.41 (95% CI, 1.3–1.52) and 1.13 (95% CI, 1.10–1.18), respectively. In another comparative study, the RA adherence to infliximab was higher than with etanercept and adalimumab 33. In contrast, in a Swiss observational cohort of patients with RA (N=2,364) treated with at least one course of anti-TNF therapy from 1997 to 2006, the discontinuation rate was significantly higher among patients treated with infliximab compared with those treated with etanercept or adalimumab 34…”
Section: Discussionmentioning
confidence: 92%
“…Além disso, poucos estudos avaliaram os MMCD biológicos adalimumabe e etanercepte 6,12,23 . Em uma revisão sistemática que incluiu estudos com pacientes em uso de biológicos anti-TNF para o tratamento da artrite reumatoide 24 , foi encontrada uma taxa semelhante de não adesão, ou seja, de um terço. O estudo de Li et al 11 foi o que encontrou maior taxa de não adesão em pacientes portadores de artrite reumatoide, sendo de 68% para o etanercepte.…”
Section: Discussionunclassified
“…Fidder et al 24 , em revisão sistemática de adesão a medicamentos biológicos na artrite reumatoide, encontraram que o sexo feminino foi o fator mais fortemente associado à ocorrên-cia de não adesão. Curkendall et al 6 também encontraram associação do sexo feminino à alta taxa de não adesão aos biológicos adalimumabe e etanercepte.…”
Section: Discussionunclassified
“…For subcutaneously administrated medication non-adherence rates up to 53.1% are reported [102]. Also, a systematic review comparing intravenous versus subcutaneous administration in the IBD and rheumatologic population showed higher non-adherence rates to subcutaneous medication [39]. Oral administration could overcome this problem even though this will require further investigations, as adherence to oral 5-ASA is low in the long-term.…”
Section: The Future Of Anti-tnf Therapymentioning
confidence: 90%
“…Indeed, mainly necessity belief, safety concerns and the quality of patient-physician relationship, and not the route of administration, influence drug adherence. Nevertheless, data from the literature remain conflicting, and higher non-adherence rates to subcutaneously administrated therapy are reported [39].…”
Section: Which Anti-tnf Agent To Choose?mentioning
confidence: 97%